Trends in Youth Participation and Leadership in Indonesia: Analysis of Youth Development Index data 2015-2023 - Muhammad Syah Fibrika Ramadhan; Wiwin Rosmawati (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study analyzes youth participation and leadership trends in Indonesia (2015–2023) using Youth Development Index (IPP) data from the Ministry of Youth and Sports. A quantitative, descriptive-analytical time-series approach was applied across 34 provinces. The results show youth social participation stabilized at 81.36% (2015–2020) but dropped significantly to 70.49% (2021–2022) due to the COVID-19 pandemic, before recovering to 71.44% in 2023. Conversely, organizational activity and meeting attendance remained stable. Striking regional disparities emerged: West Nusa Tenggara recorded the highest rate (87.31%), while DKI Jakarta recorded the lowest (38.3%). Overall, the Participation and Leadership Indicator Index stagnated at 46.67% and fell to 43.33%, reflecting suboptimal performance. The study concludes that youth development requires differentiated policy strategies based on regional characteristics, strengthening organizational ecosystems, leveraging digital transformation, and further research for effective policy interventions.